2003
DOI: 10.1007/s00428-003-0865-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of lamin A/C expression revealed by immuno-electron microscopy in dilated cardiomyopathy with atrioventricular block caused by LMNA gene defects

Abstract: Mutations of the LMNA gene encoding the lamin A and C nuclear envelope proteins cause an autosomal dominant form of dilated cardiomyopathy (DCM) with atrioventricular block (AVB). The aim of this study was to investigate ultrastructural nuclear membrane changes by conventional electron microscopy and protein expression by immuno-electron microscopy in the heart of patients with DCM and AVB due to LMNA gene mutations. Four immunohistochemical techniques were used: pre-embedding and post-embedding in Epon-Araldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 30 publications
(28 reference statements)
5
35
0
1
Order By: Relevance
“…The first two observations are likely due to specific interactions with transcriptional regulators, but the alterations in chromatin are likely due to epigenetic misregulation. Specifically dense chromatin that is normally directly apposed to the NE redistributes away from the membrane in patients with lamin-related muscular dystrophy [122,123], progeria [124] and INM protein-related NE diseases such as emerin-linked muscular dystrophy [125][126][127]. Similar alterations in chromatin organization were observed in mouse lamin depletion models [128] and transgenic mice expressing lamin point mutants associated with cardiomyopathy [129].…”
Section: Ne Diseases and Epigeneticssupporting
confidence: 53%
“…The first two observations are likely due to specific interactions with transcriptional regulators, but the alterations in chromatin are likely due to epigenetic misregulation. Specifically dense chromatin that is normally directly apposed to the NE redistributes away from the membrane in patients with lamin-related muscular dystrophy [122,123], progeria [124] and INM protein-related NE diseases such as emerin-linked muscular dystrophy [125][126][127]. Similar alterations in chromatin organization were observed in mouse lamin depletion models [128] and transgenic mice expressing lamin point mutants associated with cardiomyopathy [129].…”
Section: Ne Diseases and Epigeneticssupporting
confidence: 53%
“…These types of changes are observed in cardiomyocytes where lamin A͞C gene is abnormal (40,41). Nuclear lamins give the nucleus its shape and are involved in chromatin organization, DNA replication, gene expression, and transmission of mechanical signals from the cell surface to the nucleus (42)(43)(44)(45)(46). We found in the present study that although there was no reduction in the cellular content of lamin A͞C, there was loss of lamin A͞C from the nuclear envelope in ER␤ Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…The convoluted shapes of the nuclei, blebs, discontinuous layer of heterochromatin, and possible enlarged nuclear pores are features commonly seen in other LMNA mutations. 23,24,39 It should be kept in mind that such structural defects can also be found in DCM patients without LMNA mutations. 40 Apart from their function in nuclear stability, it has been suggested that lamin proteins are important for the structural integrity of the whole cell through interactions between nuclear lamina, the cytoskeleton, and the extracellular matrix.…”
Section: Hoorntje Et Al Mild Phenotype In Lmna P(arg331gln) Carriersmentioning
confidence: 99%